Resisting the fear of globalization and English: the IIUM experience - Abdul Manaf, Nor Faridah (Tamkang University, Taipei, 2002)
This article provides an Islamic perspective on globalization and education, based on the experience of the International Islamic University Malaysia. It cites the Quran and some prominent contemporary Islamic thinkers and writers to support the idea that plurality and multiculturalism are necessary to overcome artificial barriers of race and nation.